Circulating immune complexes detected by 125I-Clq deviation test in sera of cancer patients. - Teshima, H (1977)
The presence of circulating immune complexes in freshly drawn sera of patients with various forms of malignancies was detected by the 125I-Clq deviation test of Sobel et al. More than 50% of the 459 cancer sera showed a high inhibition of 125I-Clq uptake by sensitized sheep erythrocytes when compared with sera of 50 healthy laboratory personnel. The levels were compared with levels of total hemolytic complement and immunochemical determinations of Cl1 and C3. A correlation between high levels of circulating immune complexes and low levels of Clq was suggested. These immune complexes were separated by sucrose density gradient ultracentrifugation at low pH and were found to be heavier than 19S. Fluctuation of levels of immune complexes was evident when serial samples from the same patient were tested. Decrease of levels of immune complexes and a concomitant increase of Clq were detected after Calmette-Gueérin bacillus and autologous tumor cell treatment in some melanoma patients.